EFFECT OF NPK AND SILICON FERTILIZER ON GROWTH AND DEVELOPMENT OF Turnera ulmifolia - Mogeret, Binti Sidi; D., Omar; Hashimah, Binti Elias; Hafsah, Binti Nahrawi; Mohd Effendi, Bin Wasli (2021)
Abstract. Turnera ulmifolia is a beneficial plant commonly planted in the oil palm plantation as it easily adapts to various environmental conditions, mainly to conserve beneficial insects. Nevertheless, the planted plants were left without proper maintenance, and still few studies have been conducted on the best method in producing this plant. Thus, this study aimed to examine the effect of NPK, silicon fertilizer, and their combination on the growth and development of T. ulmifolia. Treatments including T0 Control (No Fertilization Application), T1 (0.2 g NPK), T2 (0.2 g NPK + 3.9 g silicon), T3 (0.2 g NPK + 4.9 g silicon), T4 (3.9 g silicon), and T5 (4.9 g silicon) were applied 20 days after transplanting at monthly interval for three months. Results revealed that the most significant height and the number of the branch produced were observed in T1 (0.2 g NPK) at 30, 60, and 75 days after treatment. Overall, the chlorophyll content ranged between 27.92 to 31.18 SPAD values for three observation periods. All treatments gave the same effect on morphometric measurements at 30 first day observations. After 60 days, the highest value for broad tube width and length was observed in T4, which differs significantly from other treatments. Keywords: biological control; beneficial insects; chlorophyll content; morphometric measurement s at 30 first day observations.